Indirect Restorative Materials and Techniques Selection and Used by General Dentists in Riyadh, Kingdom of Saudi Arabia - Tarek, Yasmine; AlDeghaishem, Nawar; AlNassar, Raghad; AlKhamsan, Alaa; Alzahrani, Khames T. (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Dentistry is a highly commercialized profession, constantly changing with many new technologies, techniques, and dental materials. Patients suffering from dental decay and missing teeth would like to have their teeth replaced with the most aesthetically appealing and long-lasting material and technique possible and general dental practitioners provide a significant number of indirect restorations and fixed prostheses and the following are the most commonly used categories of indirect restorations in dental practice Inlays, Onlays, Veneers and Single crowns. Objectives: The purpose of this study is to investigate the use and selection of dental material used in indirect restorations by general dental practitioners in Riyadh, Kingdom of Saudi Arabia. Methods: This is an observational cross-sectional study based on a survey, validated questionnaires by Brunton Paul in the United Kingdom. The sample size was estimated using the Qualtrics calculator with a confidence level of 95% and a margin of error of 5%; a sample size of 226 collected from March 2020 to May. Data was entered on the computer using the “Microsoft Office Excel Software” program (2016) for Mac. Data was transferred to the Statistical Package of Statistical Science Software (SPSS) program, version 20 (IBM SPSS Statistics for Windows, Version 20.0. Armonk, NY: IBM Corp.) Pearson Chi-Square and Fisher’s Exact test we used to statistically analyzed. Results: A total of 226 participants, over half the participants, were females (53.3%). The majority were Saudi nationals (91.2%) and had 1-10 years of practice since graduation (62.2%, n=140). Just under half work in private sector (47.6%) and most of the participants reported material of choice for tooth-colored Inlays and Onlays and a case with anterior veneers is laboratory fabricated porcelain (56.2%) and (45.6%) respectively. The material of choice for core build-ups in vital teeth is a light-cured composite resin in 77.4% of cases and impression materials used are addition-cured silicones in 61.9% of cases. Conclusion: Our community needs more education about oral health and indications of esthetic dental treatments and their side effects. Also, we need to increase patients’ awareness of the importance of proper treatment planning and more conservative treatment options.